Penggunaan Botes AHW sebagai Alat Siram Tetes dalam Pembudidayaan Cendana di Kabupaten Belu, NTT - Albert Husein Wawo; Rochadi Abdulhadi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
One of factors  that  causes the failure of the sandalwood cultivation in East Nusa Tenggara Province is drought of seedlings after planting. This research  has been conducted to study the use of Botes-AHW as an equipment of drip watering on sandalwood cultivation and to evaluate the water requirements in seedling growth after planting. The results  showed that   the use of water was more conserved by employing the Botes-AHW in sandalwood cultivation  than the traditional watering system.  The average of water requirements  in seedling growth (several months after planting)  is 10 liters  per seedling per month.